Review On Isolation Methods of Bio-Active Compounds from Traditional Medicinal Plants - Gokul T; Dr.N.Astalakshmi; Gowri Sankar K B; Nandhini M; Hari Hara Sudhan M R; Gowtham S; Dr.S.T.Latha; Dr.M.Surendra Kumar (International Journal of Pharma and Bio Sciences, 2022)
Herbal plants are very important in traditional use and enhance our plant biodiversity. According to the World health Organization (WHO), more than 80% of world’s population depends on traditional medicine for their primary health care needs. The sequence of Extraction and analytical technique for isolating and characterizing the bioactive compounds from plants, act as potential Lead compounds in the drug exploration process. A Broad range of Bioactive chemical compounds have been acquired from the medicinal plants as pure form (or) as Homogeneous Extract. Some plants having the medicinal value, which contain in form of chemical substances that produce a specific biological action on the Human body are called Phytochemicals. Phytochemicals in the herbal extracts for traditional use include a wide variety of bioactive metabolites of pharmaceutical and pharmacotherapeutic nature and many phytomedicines for various therapeutic areas. So, High Through put Screening programs seeking new leads in phytochemical research are gaining popularity. Today, it is very crucial to develop effective and selective methods for the isolation of those phytochemicals. The focus of the this review article includes, the brief elucidation of various Isolation techniques such as Preparative TLC, Preparative HPTLC, Preparative HPLC, Column chromatography, counter current chromatography, gas chromatography, preparative gas chromatography etc are employed in the plant extract in which the Phytochemicals compound are present and some structural examples of compounds separated using this techniques were also provided. In this article, some non chromatographic separation methods such as acid basic solvent method, dialysis method, crystallization method etc also were provided. In this article various types of Solvent System used in chromatography techniques also were given. This review covers on the various types of isolation methods of compounds from plant extracts and the various type of solvent systems used in chromatography techniques that where missed by some early articles. This review paper gives an idea about the research of those isolate compounds from the medicinal plant extracts and also gives idea about the various solvent systems used in the chromatography techniques.